Synthesis and Thermal Properties of Copper Nanoparticles - Chaudhary, Jyoti; Tailor, Giriraj; Kumar, Deepak; Joshi, Ajit (Asian Journal of Chemistry, 2017)
Copper nanoparticles have been synthesized by simple chemical precipitation method and showed versatile thermal, mechanical, magnetic and electrical properties. Copper nanoparticles have been synthesized in following two steps, in step-1st, synthesis of polymer metal complex and in 2nd step formation of copper nanoparticles. Polymer metal complex is confirmed by IR spectroscopy and XRD confirmed by size of nanoparticles is 13.13 nm, Crystal system is orthorhombic, Bravais lattice is primitive, space group pccn(56) and 2q = 42.045. Thermal stability is confirmed by TGA and the compound is very slow (rate of 3 %) loss in weight per 100 °C increase in the temperature up to 900 °C. It shows that 70 % thermal stability of the compound at 900 °C. Endothermic nature of copper nanoparticles has been confirmed by DSC.